Job Stress in Mananger Nurses, Satisfaction with Working as Managers and Intention to Leave - Ali Özkan; Filiz Kantek (Association of Nurse Managers, 2021)
Aim: This study was carried out to examine the job stress, job satisfaction and intention to leave the institution of the manager nurses. Method: This descriptive study was carried out with the participation of 100 manager nurses working in six different hospitals in a city center between June and July 2019. Data were collected using the Personal Information Form and the Perceived Job Stress Level Scale. 'SPSS 20.0' statistical package program was used in the analysis of the data. Number, Percentage, Man Whitney-U, Kruskal Wallis, Cronbach Alpha Coefficient analysis methods were used in the evaluation of the data. Results: The mean job stress level score of the manager nurses participating in the study was found to be 2.40+-0.51. It was determined that 48% of the manager nurses were satisfied with working as executive nurses and 72% of them did not consider leaving the institution. It was determined that the job stress levels of the manager nurses differed according to their satisfaction with working as a manager nurse and their intention to leave the institution (p<.005). Conclusion: It was found that the job stress levels of manager nurses were the most favorable stress level in terms of 'D' group health and productivity, and those who had the intention of leaving the institution and who were not satisfied with working as manager nurses had higher job stress.